New Pharmacological Perspectives for the Leptin Receptor in the Treatment of Obesity - Roujeau, Clara; Jockers, Ralf; Dam, Julie (Frontiers in Endocrinology, 2014)
After its discovery in 1994, leptin became the great hope as an anti-obesity treatment based on its ability to reduce food intake and increase energy expenditure. However, treating obese people with exogenous leptin was unsuccessful in most cases since most of them present already high circulating leptin levels to which they do not respond anymore defining the so-called state of “leptin resistance”. Indeed, leptin therapy is unsuccessful to lower body weight in commonly obese people but effective in people with rare single gene mutations of the leptin gene. Consequently, treatment of obese people with leptin was given less attention and the focus of obesity research shifted towards the prevention and reversal of the state of leptin resistance. Many of these new promising approaches aim to restore or sensitize the impaired function of the leptin receptor by pharmacological means. The current review will focus on the different emerging therapeutic strategies in obesity research that are related to leptin and its receptor.